A Política Pública de Transformação do Sistema Federal de Educação Profissional e Tecnológica: uma Reconfiguração Identitária do Instituto Federal de Educação Ciência e Tecnologia da Paraíba - IFPB - Souto, Maria de Fátima Dantas Carneiro (2017)
Professional education in Brazil registers, in the current historical juncture, a new scenario, based on a policy of expansion and reordering of this mode of teaching. The reordering policy of the federal network of professional education was given by the Organization of Federal Institutes of education, science and technology or, simply, Federal Institutes (IF). The Federal Institutes are several Campi institutions of higher education, professional, basic, intended to offer professional and technical education in the different methods of teaching. Were organized from the integration of two or more federal institutions professional education of a State, and the transformation of Federal Centers of technological education, Agro-technical schools and Federal technical schools linked to Federal universities. Federal Institutes fit the responsibility to promote the vertical integration of basic education to graduate; to promote the expansion of the number of campuses and the offer of courses considering the needs of the regions served. Highlights the completion of expansion management, staff and faculty, as well as the adequacy of facilities, in order to ensure the quality of education offered, all of this without losing sight of your own identity. The present study aimed to analyze the process of organization of the identity of this "new" institutionalism. We analyze the effects of institutional changes, which occurred between the period 2003 to 2010, the IFPB, whereas the vision and discourse of institutional actors. The scarcity of studies on the subject and the importance given to education by the Brazilian education policies for the current importance of this study. The research process was structured into three levels, namely: theoretical review, document analysis and field research. Field research, held at the Federal Institute of education, science and technology of Paraíba, semi-structured interviews with six institutional actors who have lived the process of transformation. The study indicates that the policy of the Organization of the Federal Institutes in Brazil, in addition to the proposal to extend the tender offer of the middle-level vocational education, represented the consolidation of a network of education intended, specifically, to the professional education and required an effort of adaptation by the same.